FACIAL TRAUMA AMONG PATIENTS WITH HEAD INJURIES. - Shazia Yasir (Journal of IMAB, 2014)
Introduction: Facial trauma is without a doubt a most challenging area for any emergency physician. Despite many researches and advances in the understanding of multiple techniques; initial assessment and management of facial injuries in emergency and early stages remained a complex area for patient care. Objective: The aim of this study is to identify the prevalence of facial trauma among patients with head injuries that may help emergency department physicians to deliver accurate and quick diagnosis and decision. Trauma to this region is often associated with mortality and morbidity and varying degree of physical and functional damage. Study Design: Prospective Cross-sectional Descriptive Study. Place and Duration of Study: Department of Emergency Medicine, Ziauddin University Hospital, Karachi from four months from Feb 2014 to May 2014. Methodology: This study was conducted at Ziauddin university hospital emergence medicine department. It is a prospective cross sectional descriptive hospital based study. 115 patients who were diagnosed of having head injuries were included in this study. Information on age, sex and cause of injury was taken for each case. Each patient was then examined for the presence of facial trauma using the CT 3D face. Data was analyzed using the SPSS program. Result: Out of 115 patients, 85 (74%) were males and 30 (26%) were females. A total of 59 (51%) patients were between 15 – 30 years of age; 26 (23%) were aged between 31 – 50; and 30 (26%) were above 51 years of age. 76% patients had facial trauma where head injuries were evident. 63% female and 80% male had facial trauma where head injuries were found in patients. Out of these 115 patients majority were involved in road traffic accidents and are from the age group 15 – 30 and predominantly male. Conclusion: Based on the study conducted; it is safe to conclude that patients who have facial trauma associate with head injuries are young males and is mainly caused by road traffic accident. The result might vary by governmental, culture or social differences.